Nasal IL‐17F is related to bronchial IL‐17F/neutrophilia and exacerbations in stable atopic severe asthma. Issue 2 (February 2015) - Sorbello, V.; Ciprandi, G.; Di Stefano, A.; Massaglia, G. M.; Favatà, G.; Conticello, S.; Malerba, M.; Folkerts, G.; Profita, M.; Rolla, G.; Ricciardolo, F. L. M.
Abstract Severe asthma (SA) is associated with neutrophil recruitment and T helper (TH)17 chemokine overexpression in bronchial biopsies. We aimed to evaluate IL‐17A and IL‐17F expression in nasal/bronchial lamina propria of atopic mild‐to‐severe asthmatics and controls in relation to neutrophilia and asthma exacerbations. Cryostat sections of nasal/bronchial biopsies obtained from 14 SA and 14 mild asthma (MA) stable atopic patients with rhinitis, and seven healthy controls were analyzed by immunohistochemistry for neutrophils, IL‐17A and IL‐17F expression. Atopic SA showed an increase in asthma exacerbations number, IL‐17F and IL‐17A expression in nasal/bronchial lamina propria compared to MA and controls, and a higher expression of bronchial neutrophils in SA compared to MA and controls. In all asthmatics, significant relationships were found between bronchial IL‐17F and neutrophils/FEV1, nasal IL‐17F and bronchial neutrophil/IL‐17 markers and between the latter and exacerbations, suggesting that nasal IL‐17F might be informative on bronchial IL17‐driven neutrophilia in atopic SA.